Power Relation in Catherine Steadman’s The Family Game - Andi Tiara Annisa Ilcham; Samtidar Samtidar; Muhammad Miftah Fauzan (State University of Makassar, 2026)
English language learning in Indonesian secondary schools continues to face challenges, particularly in developing balanced mastery of the four core language skills: listening, speaking, reading, and writing. One of the contributing factors is the limited use of interactive digital learning media that can actively engage students in the learning process. This study aims to examine students’ improvement in English achievement through the use of the Nearpod application as a digital learning medium. The study employed a pre-experimental design using a one-group pre-test and post-test model. The participants were students of SMA IT Al-Fatih Makassar who received English instruction using Nearpod-based learning activities. Quantitative data were collected through pre-test and post-test instruments covering the four English language skills. The data were analysed using descriptive statistics and inferential analysis to identify changes in students’ achievement before and after the implementation of Nearpod. The findings reveal that students demonstrated improvement in English achievement after the intervention, with more noticeable changes in listening and reading skills compared to writing and speaking skills. The results suggest that the integration of Nearpod can support students’ learning improvement, particularly in receptive language skills, within the context of English as a foreign language instruction.Keywords: English achievement, students’ improvement, Nearpod application, digital learning media, EFL